Application Of Inquiry And Discovery Learning Models To Improve Students' Motivation - Sinaga, Ika Aprilita; Hasruddin, Hasruddin; Sumarno, Sumarno (LPPM Universitas PGRI Sumatera Barat, 2024)
This study aims to determine the Application of Inquiry Learning Models and Discovery Learning to Increase Motivation in Students at UPTD Sdn 122349 Pematangsiantar. This type of research is quantitative using an experimental model (quasi-experiment). The design of this study will use a 2x2 factorial design because there are 2 sub-variables in each independent and dependent variable. To determine the classes to be studied, namely experimental group 1 and experimental group 2 in class V at UPTD SD Negeri 122349 Pematangsiantar using a simple random sampling method. Based on the results of the analysis and discussion in this study, several conclusions are put forward as follows: There are differences in science learning outcomes in students taught with inquiry and Discovery learning models in class V students at UPTD SDN 122349 Pematangsiantar. There are differences in science learning motivation in students taught with inquiry and Discovery learning models in class V students at UPTD SDN 122349 Pematangsiantar. There is an interaction between the learning model and learning motivation in influencing science learning outcomes in grade V students at UPTD SDN 122349 Pematangsiantar. There is no interaction between the learning model and learning outcomes in influencing science learning motivation in grade V students at UPTD SDN 122349 Pematangsiantar.